Parenting Mothers with Stunting Toddlers at Banjangkaran II Community Health Center: A Qualitative Study - Natanagara, I Gede Catur Wira; Putu Wiliska Wilasitha (HM Publisher, 2022)
Stunting is an overview of stunted growth as a result of a lack of nutrient intake in the long term. According to the WHO Child Growth Standard, stunting is based on the index of body length for age (PB/U) or height for age (TB/U) with a limit (z-score) of less than -2 SD. This study will describe the pattern of parenting and the incidence of stunting in toddlers with UPTD. Banjarangkan II Community Health Center. This research is an observational study using a qualitative approach with a cross-sectional study design. This research was conducted on 8 mothers of stunting toddlers in the UPT working area. Banjarangkan II Community Health Center The instruments used in this study was an in-depth interview guide and observations on feeding habits, parenting habits, hygiene habits, and habits of receiving health services, as well as measuring children's height. In this study, it was found that the parenting pattern of mothers with stunting toddlers was still not good, seen in the habits of feeding, caregiving, hygiene, and getting health services. It is necessary to increase a mother's knowledge about parenting, both from feeding habits, caregiving, hygiene, and getting health services.